Clinical features and treatment outcomes of fibrous dysplasia: a report from the Bone and Soft Tissue Tumor Registry in Japan - Masayuki Morishita; Daisuke Kobayashi; Akira Ogose; Akira Kido; Akihiko Takeuchi; Kazu Matsumoto; Kota Watanabe; Yoji Furukawa; Michio Ozeki; Akira Kawai; Yoshihiro Nishida (Japanese Journal of Clinical Oncology, 2026)
Abstract Background Fibrous dysplasia (FD) is a benign bone disorder classified into monostotic (MFD) and polyostotic (PFD) forms. There is limited evidence available regarding the clinical management of FD, and no large-scale epidemiological or treatment reports have been published from Japan. Therefore, this study aimed to clarify FD epidemiology and management using data from the nationwide Bone and Soft Tissue Tumor (BSTT) Registry. Methods This study retrospectively analyzed patients with MFD and PFD registered in the BSTT Registry between 2008 and 2019. The data included patient demographics, tumor location, surgical treatment, and recurrence. Local control survival (LCS) was estimated using the Kaplan–Meier method and compared using a log-rank test Results In total, 3181 FD cases were registered from 127 institutions (MFD, 2889; 90.8%; PFD, 292; 9.2%). The femur was the most frequently affected site in both groups. Intralesional curettage was the most frequently performed surgical procedure, accounted for in 66.9% of MFD cases and 60.8% of PFD cases. Local recurrence occurred in 2.6% and 4.2% of patients with MFD and PFD, respectively. The 1-year overall LCS rate was 97.4%, with no significant differences between groups. Conclusion This study provides the largest dataset of FD in Japan, contributing to a better understanding of its epidemiology and surgical management. However, limitations, such as the underrepresentation of pediatric cases, incomplete data on non-surgical treatments, and deformity correction procedures, highlight the need for more comprehensive data to inform future treatment strategies.